2010
DOI: 10.1111/j.1523-1739.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Depression Accumulation across Life‐History Stages of the Endangered Takahe

Abstract: Studies evaluating the impact of inbreeding depression on population viability of threatened species tend to focus on the effects of inbreeding at a single life-history stage (e.g., juvenile survival). We examined the effects of inbreeding across the full life-history continuum, from survival up to adulthood, to subsequent reproductive success, and to the recruitment of second-generation offspring, in wild Takahe ( Porphyrio hochstetteri ) by analyzing pedigree and fitness data collected over 21 breeding seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 32 publications
5
100
0
Order By: Relevance
“…By foregoing the cost of reproduction on survival (M8) and subsequent fecundity (M10), the net effect of a female's inbreeding coefficient on LBS is diminished, and so was undetectable among those who bred at least once (M12). Similar discrepancies between effects on annual or seasonal and lifetime measures of fitness due to compensation can be found, for example, when inbreeding affects brood success in birds, but inbred females increase the number of breeding attempts (35). These results emphasize the importance of considering the entire life cycle, including effects of parental inbreeding coefficients on juvenile survival, when estimating the total effect of inbreeding depression.…”
Section: Inbredmentioning
confidence: 55%
“…By foregoing the cost of reproduction on survival (M8) and subsequent fecundity (M10), the net effect of a female's inbreeding coefficient on LBS is diminished, and so was undetectable among those who bred at least once (M12). Similar discrepancies between effects on annual or seasonal and lifetime measures of fitness due to compensation can be found, for example, when inbreeding affects brood success in birds, but inbred females increase the number of breeding attempts (35). These results emphasize the importance of considering the entire life cycle, including effects of parental inbreeding coefficients on juvenile survival, when estimating the total effect of inbreeding depression.…”
Section: Inbredmentioning
confidence: 55%
“…As purging of highly deleterious mutations is more efficient than purging of mildly deleterious mutations, other things being equal, the high inbreeding depression of egg viability in the PT population is surprising. Other studies have previously reported that purging may not effectively reduce inbreeding depression in all traits (63,64).…”
Section: Discussionmentioning
confidence: 88%
“…Our set of candidate models was defined as those with DAIC B 2. The ''natural'' average was used in model averaging (Burnham & Anderson, 2002;Grueber et al, 2010). This analysis produces two outputs: parameter estimates (and their unconditional standard errors, which incorporate model-selection uncertainty) and the relative importance of each variable in explaining the variance in the response variable.…”
Section: Statistical Analysesmentioning
confidence: 99%